Novel Aspects of Insulin-like Growth Factor 1/insulin Network in Chronic Inflammatory Airway Disease - Ruan, Wenjing; Deng, Jing; Ying, Kejing (Current Medicinal Chemistry, 2020)
At least a proportion of patients suffering from chronic inflammatory airway diseases respond poorly to the bronchodilator and corticosteroid therapies. There is a need for the development of improved anti-inflammatory treatment. Insulin Growth Factor 1 (IGF1) and insulin participate in not only metabolism and glucose homeostasis, but also many other physiological and pathophysiological processes, including growth and inflammation. Recently, it was shown that not only the classical IGF1 and IGF1 Receptor (IGF1R), but also the other molecules in the IGF1/insulin network, including insulin, insulin-like growth factor-binding protein (IGFBP), and IGFBP protease, have roles in chronic inflammatory airway diseases. This review aims to provide a comprehensive insight into recent endeavors devoted to the role of the IGF1/insulin network in chronic inflammatory airway diseases. Its participation in airway inflammation, remodeling, and hyper-responsiveness (AHR), as well as acute exacerbation, has been conclusively demonstrated. Its possible relation to glucocorticoid insensitivity has also been indicated. A better understanding of the IGF1/insulin network by further bench-to-bedside research may provide us with rational clinical therapeutic approaches against chronic inflammatory airway diseases.
Keywords: COPD